2016
DOI: 10.3928/1081597x-20160121-02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Limbal Relaxing Incisions on Corneal Aberrations

Abstract: Limbal relaxing incision is an effective method in reducing corneal astigmatism with neutral effect on corneal aberrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Moreover, 21.3-22.4% of patients with cataract have 1.00 dioptre (D) to 1.50 D of corneal astigmatism, with 10.6% to 12.4% of patients having 1.50 D to 2.00 D and 8.20% to 13.0% of patients having 2.00 D or more [1,2]. Compared with the conventional approaches, like corneal relaxing incisions (CRI), limbal relaxing incisions (LRI) and laser-assisted in situ keratomileusis (LASIK) [3][4][5], toric intraocular lens (IOL) has become an increasingly common technique due to its great advantages in predictability, stability and safety.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 21.3-22.4% of patients with cataract have 1.00 dioptre (D) to 1.50 D of corneal astigmatism, with 10.6% to 12.4% of patients having 1.50 D to 2.00 D and 8.20% to 13.0% of patients having 2.00 D or more [1,2]. Compared with the conventional approaches, like corneal relaxing incisions (CRI), limbal relaxing incisions (LRI) and laser-assisted in situ keratomileusis (LASIK) [3][4][5], toric intraocular lens (IOL) has become an increasingly common technique due to its great advantages in predictability, stability and safety.…”
Section: Introductionmentioning
confidence: 99%
“…Overcorrections are unusual under correction to occur. Limbal relaxing incisions also known to have a neutral effect on corneal aberrations [7]. Another study revealed aberration was significantly increased in the limbal The postoperative uncorrected visual acuity at 4 weeks 0.0±0.15 with a best corrected visual acuity was 0.0±0.1.…”
Section: : Uncorrected Visual Acuity Preoperatively and Postoperativelymentioning
confidence: 97%
“…Advancements in preoperative diagnostic tests and surgical techniques, as well as increased availability of premium intraocular lens (IOL) implants, have escalated patient expectations, thus making accurate management of preexisting astigmatism mandatory in order to deliver optimal visual outcome. Astigmatism management in studied issue, and many techniques are available for its correction, namely relaxing incisions (LRIs), arcuate keratotomies, toric intraocular lenses (IOL), paired incisions on the steep axis or subsequent excimer laser ablation t 20% of all cataract patients have clinically significant astigmatism, usually Though Limbal relaxing incisions are known to be effective in correcting corneal astigmatism diopters, recent studies indicate that it can be used to correct corneal astigmatism upto the level of 2.5 D. It works well when performed during phacoemulsification and can be used independently to correct surgically induced astigmatism as well [7].…”
Section: : Uncorrected Visual Acuity Preoperatively and Postoperativelymentioning
confidence: 99%
See 2 more Smart Citations